1993
DOI: 10.1111/j.1399-6576.1993.tb03791.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of nitrous oxide on recovery of bowel function after abdominal hysterectomy

Abstract: The influence of nitrous oxide on the recovery of bowel function was studied in 36 patients anaesthetised for elective abdominal hysterectomy with or without salpingo-oophorectomy. Patients were randomly assigned to receive either isoflurane in nitrous oxide and 30% oxygen (N2O group) or isoflurane in air and 30% oxygen (Air group). Anaesthetic management included thiopentone, fentanyl, suxamethonium and atracurium. The lungs were not ventilated prior to intubation. Before closing the abdomen, the surgeon asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…This left 30 reports including 4598 patients (2297 in the N 2 O group and 2301 in the non‐N 2 O group) [39, 41–63]. The characteristics of each group, when pooled, are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…This left 30 reports including 4598 patients (2297 in the N 2 O group and 2301 in the non‐N 2 O group) [39, 41–63]. The characteristics of each group, when pooled, are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…This is one of the longest periods of nitrous oxide exposure among the trials we evaluated. Some of the negative results were observed in shorter procedures [16,21] and it remains likely that nitrous oxide does not produce clinically important bowel distension in operations of short duration. As a methodological issue, other than Lewis [7] and Boulanger and Hardy [13], none of the investigators quantified bowel distension by measuring girth or intestinal circumference; instead, the surgeons blinded to the study protocol, usually rated it in terms of the clinically relevant parameter (i.e.…”
Section: Discussion and Authors' Opinionmentioning
confidence: 92%
“…O n the other hand, there are studies where no such effects were observed caused by nitrous oxide, for instance when propofol anaesthesia was combined with N20 (8)(9). In women undergoing hysterectomy with isoflurane anaesthesia, nitrous oxide caused no other adverse effects than a clinically insignificant delayed passing of faeces (10). However, when elderly patients are scheduled for a long-lasting laparotomy because of bowel obstruction with distension, it may be wise to avoid the administration of nitrous oxide.…”
Section: Nitrous Oxide and Bowelandnctionmentioning
confidence: 99%